Efektivitas Penggunaan Metode Counseling Learning Method (CLM) untuk Meningkatkan Kemahiran Berbicara - Aidillah Suja; Cahya Edi Setyawan (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2021)
This study aims to determine the Implementation Methods Counseling Learning Method to improve speaking skills for second-grade students of MTs Al-Muhajirin Tapung and determine the factors that influence the adoption of the Counseling Learning Method. This study is a research experiment, experimental research is a research method that is used to search for a specific treatment effect against the other in uncontrolled conditions. By using experimental design Pretest – Posttest None Control Group Design. Ways of data collection are observation and an oral test. The results of the analysis of the data obtained on the Application Methods Counseling Learning Method in Learning Arabic to improve speaking skills for second-grade students of MTs Al-Muhajirin Tapung based on observations obtained 95.8% means